Comparison of bench‐scale decortication devices to fractionate bran from sorghum. Issue 5 (20th August 2018) - Hums, Megan E.; Moreau, Robert A.; Yadav, Madhav P.; Powell, Michael J.; Simon, Stefanie
Abstract: Background and objectives: Decortication of sorghum grain separates its pericarp (bran) from the endosperm which could have beneficial impacts on ethanol production while producing value‐added coproducts. The goal of this study was to compare three bench‐scale devices (barley pearler, scarifier, and rice polisher) to decorticate sorghum grain and analyze the composition of each fraction. Findings: The scarifier and barley pearler produced bran with similar contents of protein (~10%), starch (~40%), and total dietary fiber (~40%). In a single batch to produce 10% (w/w) bran, the scarifier processed more sorghum to produce more bran (12 g/150 g) than the barley pearler (7 g/75 g). The rice polisher produced bran (43 g/500 g) with higher content of oil (~12%), protein (~11%), ash (~6%), and starch (~47%), but total dietary fiber was lower (~29%). The scarifier bran had the highest wax content (1.9%), while the rice polisher and barley pearler brans had similar lower wax content (1.6%). Conclusions: The composition of bran from the rice polisher indicated that more germ and some endosperm were removed during decortication as compared to the other devices. Significance and novelty: There is a need for producing bran between laboratory‐ and pilot‐scale with efficient separation of the pericarp from the endosperm. This research is the first to compare the composition of all sorghum fractions, including a wax analysis, from three types of bench‐scale decortication devices.